HUBUNGAN ANTARA PENGUASAAN KOSA KATA DAN KEMAMPUAN BERBICARA SISWA KELAS IX SMP NEGERI 1 KUNTO DARUSSALAM - Faldayani, Dilla; Supriusman, Supriusman; Mahsyur, Mahsyur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This present study was aimed to find out wheter there was a correlation between vocabulary mastery and speaking ability of the third year students of SMP Negeri 1 Kunto Darussalam. The population this research was the third year students of SMP Negeri 1 Kunto Darussalam. The sample was chosen by using cluster random sampling and there were IX 2 and IX 4 as the samples. Vocabulary test was used to know the students? vocabulary mastery whilespeaking test was used to know the students? speaking ability in describing place. The obtained data were analyzed by using Pearson Product Moment?s Formula usingSPSS 23.00 program. The results revealed that the coefficient correlation is 0.729 with a significant of 0.000. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. In conclusion, there was a significant correlation between vocabulary mastery and speaking ability of the third year student of SMP Negeri 1Kunto Darussalam. Key Words: Correlation, Vocabulary Mastery, Speaking Ability